A PERMA-nent solution to understanding psychological wellbeing? Exploring the utility of the PERMA model in a university workplace - Ng, Xiao Hui; Chu, Jeanie; Doshi, Kinjal (Frontiers in Psychology, 2025)
IntroductionA diagnosis of a psychological health concern is associated with lower wellbeing and subjective quality of life (sQoL). However, there is limited literature examining whether individuals who suspect they have a psychological health condition (SPHC) experience similar challenges. The primary aim of this study is to investigate the relationship between SPHC, workplace wellbeing, and sQoL, with the goal of informing future workplace wellbeing interventions within a diverse university setting. A secondary aim is to explore whether additional aspects of wellbeing are valued by a multicultural population beyond the five core components defined in Martin Seligman’s Wellbeing Theory: positive emotion, engagement, relationships, meaning, and achievement.MethodsA 57-item survey was sent to a randomly generated list of 2,000 university staff to request for their participation. It gathered information on their understanding of wellbeing, presence of suspected psychological health conditions, level of distress, workplace psychological wellbeing, and quality of life.ResultsFirst, individuals with SPHCs reported significantly lower levels of wellbeing and sQoL compared to those who did not suspect having a PHC. Second, workplace wellbeing was found to mediate the relationship between psychological distress and sQoL. Finally, qualitative analysis revealed five additional lay conceptualizations of wellbeing in addition to the five facets identified in PERMA, namely psychological health, physical health, balance, meeting basic needs, and autonomy.DiscussionThat wellbeing mediates the relationship between psychological distress and sQoL suggests that workplace wellbeing interventions may be particularly important in improving sQoL, especially in individuals who experience SPHCs given that they also experience lower sQoL. That five other lay conceptualisations of wellbeing also emerged from the findings suggests that laypeople’s understanding of wellbeing adds a unique cultural and situational lens to the current understanding of this construct. Further implications are discussed.